A new method to predict the in-hospital outcome of multi-trauma patients: R-GAP - Sepehri Majd, Pegah; Alimohammadi Siyabani, Amirhossein; Ebrahimi Bakhtavar, Haniyeh; Rahmani, Farzad (Journal of emergency practice and trauma, 2022)
Objective: Awareness of the severity of trauma and the outcome of patients can help physicians decide how long to treat patients. The objective of this study is to design a new score (R-GAP: Revised-GCS, Age, Pressure) for multi-trauma patients and determine its predictive value concerning in-hospital outcome of these patients. Methods: This cross-sectional study was performed in the emergency ward of Imam Reza (AS) and Shohada hospitals (referral centers for trauma patients) affiliated to Tabriz University of Medical Sciences from 2019 to 2020. The sample size of this study was estimated to be 2000 people. Required information was collected and the final diagnosis of the patients was recorded. The hospital outcome was recorded at the time of discharge. Patients’ outcome was also recorded using the Glasgow Outcome Scale (GOS) system. Based on the obtained data, GAP, R-GAP, new trauma score (NTS) scores were also collected and their results were compared with the designed model. Receiver operating characteristic (ROC) curve and logistic regression were used to analyze the predictive value of the scores. Results: The mean age of the subjects was 34.09 (± 15.23) years. The highest outcome of patients based on the GOS system was recovery, moderate disability, and severe disability with 1309 cases (54.9%), 743 cases (31.2%), and 212 cases (8.9%), respectively. The mean of GAP, R-GAP, and NTS scores were 21.83 (± 3.1), 21.47 (± 3.4), and 21.27 (± 3.3), respectively. The intensity of GAP, R-GAP, and NTS in most subjects was low with 2143 cases (89.9%), 1994 cases (83.6%), and 2138 cases (89.7%). Among the significant variables included in the regression model, O2sat, primary GCS, GAP, R-GAP, and NTS with modulation on other variables, significantly equalized the mortality chance by 0.416, 0.622, 0.595, 0.601, 0.637, respectively (P value<0.001). Conclusion: According to the study results, it seems that GAP, R-GAP, and NTS respectively, have the highest strength of predictive value in the survival of patients with multiple traumas. It is suggested that a comprehensive study be conducted to better estimate this issue.